Diseño de un Ambiente Virtual de Aprendizaje dirigido a personas en condición de discapacidad intelectual moderada para fortalecer el proceso de lectura inferencial (2020)
The main objective of this work is to reflect on the design of specialized material with the teaching and learning process in people with moderate intellectual disabilities in order to strengthen the level of inferential reading through a virtual learning environment, attending to the specific needs of the study population. This material was subjected to a pilot test with a 16 years old student diagnosed with moderate intellectual disability due to fragile X syndrome. For the design of the material, aspects related to public language policies, expert authors in inferential reading and scientific theories on the target population regarding their teaching-learning process and linguistic needs were taken into account. Finally, some considerations and reflections were identified to take into account as language teachers during this learning process.